A novel method to grip a golf club for a quadruple amputee golfer. Issue 3 (September 2016) - Wood, Paul; Henrikson, Erik; Lewis, Jeff
Abstract A device was created to enable a quadruple amputee golfer to securely hold a golf club and play the game. The device also offers a way to easily and independently switch one golf club for another during the round. It comprises a spring-loaded cylindrical fixture to hold the club to the prosthetic arm and a J-slot to twist and release the club to exchange it for a different club on the course. The device has been used to play golf for 5 years. The engineered solution attaches to the golfer's right arm and he swings using a right-handed stance. It includes a bend in the prosthetic arm to enable a more functional golf swing. A series of club fittings were conducted over a number of years and experiments were conducted on both driving ranges and golf courses with the aim of optimizing performance. The complete set of club specifications is included along with typical shot results for selected clubs.